In-situ hard carbon coating on surface of graphite workpiece and preparation method of in-situ hard carbon coating

The ZIF-8 coating is constructed on the surface of graphite workpieces through electrochemical deposition and in-situ solid phase reaction, and through high-temperature carbonization treatment, the problem of difficulty in constructing a porous hard carbon coating in the prior art is solved, and efficient and pure coating preparation is achieved, and the performance of graphite workpieces is improved.

CN119504285APending Publication Date: 2025-02-25INDAF ADVANCED MATERIALS (SUZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411682415.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

It is difficult to efficiently construct a hard carbon coating with a porous structure on the surface of graphite workpieces in the prior art, and traditional coating methods have problems with the use of binders and the introduction of impurities.

Method used

Zinc oxide was deposited on the surface of graphite workpiece by electrochemical deposition, and then ZIF-8 coating was formed by in-situ solid phase reaction with 2-methylimidazole, and a porous hard carbon coating was obtained by high-temperature carbonization treatment.

Benefits of technology

The porous hard carbon coating is grown in situ on the surface of the graphite workpiece, avoiding the use of binder, improving the bonding and purity of the coating, and enhancing the mechanical properties and gas adsorption efficiency of the graphite workpiece.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005148681050000061
    Figure BDA0005148681050000061
  • Figure BDA0005148681050000071
    Figure BDA0005148681050000071
  • Figure HDA0005148681060000011
    Figure HDA0005148681060000011
Patent Text Reader

Abstract

The invention provides an in-situ hard carbon coating for the surface of a graphite workpiece, the hard carbon coating is a carbon coating derived from a ZIF-8 coating after high-temperature carbonization, and the ZIF-8 coating is prepared from a zinc oxide coating electrochemically deposited on the surface of the graphite workpiece and 2-methylimidazole through an in-situ solid-phase reaction. According to the in-situ synthesis method, use of a binder in the traditional carbon coating coating process is avoided, meanwhile, good coating bonding performance is achieved, in addition, the porous structure inherited from ZIF-8 changes the pore channel structure of the surface of the graphite workpiece, and the specific surface area of the surface part of the graphite workpiece is increased. The method is efficient and easy to implement and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of graphite materials, and in particular relates to an in-situ hard carbon coating on the surface of graphite derived from a zeolite imidazolate skeleton structural material and a preparation method thereof. Background Art

[0002] Zeolite imidazolate framework material (ZIF), as a type of metal organic framework compound (MOF), is a porous crystalline material composed of metal ions as coordination centers and imidazolates constructed through coordination bonds. Its derived carbon, as a kind of hard carbon, can inherit the porous structure of its precursor ZIF after pyrolysis. It has the characteristics of large specific surface area, regular pore structure, high porosity and excellent adsorption performance. It has a wide range of applications in energy storage and conversion, gas separation and other fields. Constructing a ZIF-derived carbon coating on the surface of a graphite workpiece can not only improve the mechanical properties of the graphite workpiece surface, reduce the loss of the graphite workpiece during use, and extend the service life of the graphite workpiece, but also use the porous structure of the ZIF-derived carbon coating to achieve efficient adsorption of internal reaction exhaust gases in high-temperature reactors, vapor deposition furnaces, etc. Electrochemical deposition refers to the use of electrochemical reactions (such as reduction or oxidation) to form a deposition layer of metal ions or other substances in the solution on the surface of the substrate. Compared with traditional mechanical coating, the electrochemical deposition layer can form a chemical bond with the substrate, with strong bonding force and avoid the use of adhesives. Using electrochemical deposition and subsequent chemical reactions to construct a carbon coating on a graphite workpiece can improve the adhesion of the coating and avoid the introduction of other impurities, which is beneficial to improving the overall purity of the graphite workpiece. Summary of the invention

[0003] Technical problem to be solved: The present invention provides a method for preparing an in-situ hard carbon coating on the surface of a graphite workpiece, and constructs a carbon coating with a porous structure and adjustable hardness on the surface of the graphite workpiece by in-situ growth.

[0004] Technical solution: An in-situ hard carbon coating on the surface of a graphite workpiece: the hard carbon coating is a carbon coating derived from a graphitized ZIF-8 coating, and the ZIF-8 coating is prepared by an in-situ solid phase reaction of a zinc oxide coating electrochemically deposited on the surface of the graphite workpiece and 2-methylimidazole. An in-situ hard carbon coating on the surface of a graphite workpiece, the preparation method comprising the following steps: S1. placing the cleaned graphite workpiece in an electrolyte and depositing zinc oxide on its surface by electrochemical deposition; S2. The graphite workpiece obtained in S1 was cleaned and dried, and then the surface was covered with ground 2-methylimidazole powder and placed in a sealed container for reaction; S3. The graphite workpiece obtained in S2 is cleaned and dried, and then the graphite workpiece is heat-treated under the protection of an inert gas to obtain a graphite workpiece with a porous hard carbon coating. Preferably, the method for preparing the electrolyte in S1 comprises the following steps: S11. Add zinc chloride, potassium chloride and sodium dodecyl sulfate in a molar ratio of 5 to 10:10 to 50:0.5 to 1 to water and heat in a water bath, and stir to obtain a homogeneous solution; S12. Pass oxygen into the homogeneous solution and continue stirring for 0.5 to 1.5 hours to obtain an electrolyte. Preferably, the mass fraction of the homogeneous solution in S11 is 10-35wt%. Preferably, the electrochemical deposition method in S1 is a constant potential method or a constant current method, the potential of the constant potential method is -1.5 to -0.8 V (vs. SCE), the time is 5 to 15 min, the working electrode of the constant current method is the anode, and the current density is 10 to 100 mA / cm 2 , time is 5 to 20 minutes. Preferably, the particle size of the 2-methylimidazole powder after grinding in S2 is 50-200 μm, and the coverage of the 2-methylimidazole powder is 0.05-0.2 g / cm 2 The reaction temperature is 160-175°C and kept warm for 5-20 minutes. Preferably, the heat treatment temperature in S3 is 1100-2200° C., and the heat treatment time is 2-4 hours. Beneficial effects: 1. The present invention generates a porous hard carbon coating in situ on the surface of a graphite workpiece by a method of electrochemical deposition-solid phase conversion-high temperature carbonization, thereby avoiding the use of a binder, improving the purity of the graphite workpiece, and the coating has good bonding properties and is easy to prepare; 2. The hard carbon coating obtained by carbonization of ZIF-8 has a porous structure. The coating can not only improve the mechanical properties of the graphite product surface and extend its service life, but also increase the specific surface area of ​​the graphite workpiece surface and improve its surface gas adsorption efficiency, which is beneficial to the application of graphite products such as tail gas collection, gas separation, and gas flow field control; 3. The porous hard carbon coating prepared by the present invention can achieve efficient adjustment of its thickness, morphology, etc. by controlling the conditions of electrochemical deposition, so as to facilitate the preparation of products with different coating requirements. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 It is a flow chart of the preparation of an in-situ hard carbon coating on the surface of a graphite workpiece provided by the present invention; Figure 2 is a scanning electron microscope image of zinc oxide on the graphite surface obtained after performing step 102; Figure 3is a scanning electron microscope image of ZIF-8 on the graphite surface obtained after performing step 103. DETAILED DESCRIPTION The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments: Example 1 An in-situ hard carbon coating on the surface of a graphite workpiece, the preparation method comprising the following steps: S1. The cleaned graphite workpiece is placed in an electrolyte, and zinc oxide is deposited on its surface by constant potential electrochemical deposition at a potential of -1.5 V (vs. SCE) for 5 min; S2. The graphite workpiece obtained in S1 was cleaned and dried, and then covered on its surface with 2-methylimidazole powder with a particle size of 50 μm, and the coverage of 2-methylimidazole powder was 0.05 g / cm 2 , and placed in a sealed container and reacted at 160°C for 5 min; S3. The graphite workpiece obtained in S2 is cleaned and dried, and then the graphite workpiece is heat treated at 1100°C for 2h under an inert gas protection to obtain a graphite workpiece with a porous hard carbon coating; The preparation method of the electrolyte in S1 comprises the following steps: S11. Add zinc chloride, potassium chloride and sodium dodecyl sulfate in a molar ratio of 5:10:0.5 to water and heat in a water bath, and stir to obtain a homogeneous solution with a mass fraction of 10 wt%; S12. Pass oxygen into the homogeneous solution and continue stirring for 0.5 h to obtain an electrolyte. Example 2 An in-situ hard carbon coating on the surface of a graphite workpiece, the preparation method comprising the following steps: S1. The cleaned graphite workpiece is placed in an electrolyte, and zinc oxide is deposited on its surface by constant potential electrochemical deposition at a potential of -0.8 V (vs. SCE) for 15 min; S2. The graphite workpiece obtained in S1 was cleaned and dried, and then covered on its surface with 2-methylimidazole powder with a particle size of 200 μm, and the coverage of 2-methylimidazole powder was 0.2 g / cm 2 , and placed in a sealed container and reacted at 175°C for 20 min; S3. The graphite workpiece obtained in S2 is cleaned and dried, and then the graphite workpiece is heat treated at 2200°C for 4h under an inert gas protection to obtain a graphite workpiece with a porous hard carbon coating; The preparation method of the electrolyte in S1 comprises the following steps: S11. Add zinc chloride, potassium chloride and sodium dodecyl sulfate in a molar ratio of 10:50:1 into water and heat in a water bath, and stir to obtain a homogeneous solution with a mass fraction of 35 wt%; S12. Pass oxygen into the homogeneous solution and continue stirring for 1.5 hours to obtain an electrolyte. Example 3 An in-situ hard carbon coating on the surface of a graphite workpiece, the preparation method comprising the following steps: S1. The cleaned graphite workpiece is placed in an electrolyte, and zinc oxide is deposited on its surface by constant potential electrochemical deposition, the potential is -1.0 V (vs. SCE), and the deposition time is 8 min; S2. The graphite workpiece obtained in S1 was cleaned and dried, and then covered on its surface with 2-methylimidazole powder with a particle size of 100 μm, and the coverage of 2-methylimidazole powder was 0.1 g / cm 2 , and placed in a sealed container and reacted at 165°C for 10 min; S3. The graphite workpiece obtained in S2 is cleaned and dried, and then the graphite workpiece is heat treated at 1300°C for 3h under an inert gas protection to obtain a graphite workpiece with a porous hard carbon coating; The preparation method of the electrolyte in S1 comprises the following steps: S11. Add zinc chloride, potassium chloride and sodium dodecyl sulfate in a molar ratio of 8:10:0.5 to water and heat in a water bath, and stir to obtain a homogeneous solution with a mass fraction of 15 wt%; S12. Pass oxygen into the homogeneous solution and continue stirring for 1.0 h to obtain an electrolyte. Example 4 An in-situ hard carbon coating on the surface of a graphite workpiece, the preparation method comprising the following steps: S1. The cleaned graphite workpiece is placed in an electrolyte, and zinc oxide is deposited on its surface by constant potential electrochemical deposition at a potential of -1.5 V (vs. SCE) for 5 min; S2. The graphite workpiece obtained in S1 was cleaned and dried, and then covered on its surface with 2-methylimidazole powder with a particle size of 150 μm, and the coverage of 2-methylimidazole powder was 0.15 g / cm 2 , and placed in a sealed container and reacted at 170°C for 15 min; S3. The graphite workpiece obtained in S2 is cleaned and dried, and then the graphite workpiece is heat treated at 1500°C for 2h under an inert gas protection to obtain a graphite workpiece with a porous hard carbon coating; The preparation method of the electrolyte in S1 comprises the following steps: S11. Add zinc chloride, potassium chloride and sodium dodecyl sulfate in a molar ratio of 5:18:0.5 to water and heat in a water bath, and stir to obtain a homogeneous solution with a mass fraction of 30wt%; S12. Pass oxygen into the homogeneous solution and continue stirring for 0.5 h to obtain an electrolyte. Example 5 An in-situ hard carbon coating for a graphite surface, the preparation method comprising the following steps: S1. Place the cleaned graphite workpiece in an electrolyte and deposit zinc oxide on its surface using a constant current electrochemical deposition method with a current density of 10 mA / cm 2 , the deposition time is 15min; S2. The graphite workpiece obtained in S1 was cleaned and dried, and then covered on its surface with 2-methylimidazole powder with a particle size of 120 μm, and the coverage of 2-methylimidazole powder was 0.15 g / cm 2 , and placed in a sealed container and reacted at 170°C for 12 minutes; S3. The graphite workpiece obtained in S2 is cleaned and dried, and then the graphite workpiece is heat treated at 1700°C for 2h under an inert gas protection to obtain a graphite workpiece with a porous hard carbon coating; The preparation method of the electrolyte in S1 comprises the following steps: S11. Add zinc chloride, potassium chloride and sodium dodecyl sulfate in a molar ratio of 10:17:0.5 to water and heat in a water bath, and stir to obtain a homogeneous solution with a mass fraction of 20wt%; S12. Pass oxygen into the homogeneous solution and continue stirring for 0.5 h to obtain an electrolyte. Example 6 An in-situ hard carbon coating for a graphite surface, the preparation method comprising the following steps: S1. Place the cleaned graphite workpiece in an electrolyte and deposit zinc oxide on its surface using a constant current electrochemical deposition method with a current density of 100 mA / cm 2 , the deposition time is 20min; S2. The graphite workpiece obtained in S1 was cleaned and dried, and then covered on its surface with 2-methylimidazole powder with a particle size of 170 μm, and the coverage of 2-methylimidazole powder was 0.05 g / cm 2 , and placed in a sealed container and reacted at 170°C for 15 min; S3. The graphite workpiece obtained in S2 is cleaned and dried, and then the graphite workpiece is heat treated at 1800°C for 2h under an inert gas protection to obtain a graphite workpiece with a porous hard carbon coating; The preparation method of the electrolyte in S1 comprises the following steps: S11. Add zinc chloride, potassium chloride and sodium dodecyl sulfate in a molar ratio of 5:22:0.5 to water and heat in a water bath, and stir to obtain a homogeneous solution with a mass fraction of 22 wt%; S12. Pass oxygen into the homogeneous solution and continue stirring for 0.5 h to obtain an electrolyte. Comparative Example 1 The difference between this comparative example and Example 6 is that the epoxy resin is coated on the surface of the workpiece by a brushing method, and the workpiece is carbonized at high temperature to obtain a graphite workpiece with an epoxy resin-derived hard carbon coating. The preparation method comprises the following steps: S1. Mix E51 epoxy resin and curing agent in a ratio of 70:30, and evenly apply it on the surface of the cleaned and dried graphite workpiece, and cure it at 120℃ for 4h. The coating amount of epoxy resin is 0.05g / cm 2 ; S2. The graphite workpiece obtained in S1 is heat treated at 1100° C. for 2 h under inert gas protection to obtain a graphite workpiece with epoxy resin-derived hard carbon. Comparative Example 2 The difference between this comparative example and Example 6 is that a hard carbon coating is prepared on the surface of the workpiece by using a conventional brushing method and epoxy resin as a binder. The preparation method comprises the following steps: S1. 9.87 mmol of zinc nitrate hexahydrate and 79.4 mmol of 2-methylimidazole were dissolved in 200 mL of methanol respectively; under stirring, the zinc nitrate hexahydrate solution was quickly poured into 2-methylimidazole, stirred at room temperature for 1 h, centrifuged at 12000 rpm, washed with methanol 4 times, and vacuum dried at 60°C for 12 h to obtain ZIF-8; S2. Mix the ZIF-8 obtained in S1 with E51 epoxy resin in a mass ratio of 1:10. After mixing evenly, add curing agent, and the ratio of epoxy resin to curing agent is 70:30. Mix evenly again and apply it evenly on the surface of the cleaned and dried graphite workpiece, and cure it at 120℃ for 4h. The coating amount of the mixture is 0.06g / cm 2 ; S3. The graphite workpiece obtained in S2 is heat treated at 1100° C. for 2 h under inert gas protection to obtain a graphite workpiece with ex-situ ZIF-8 derived hard carbon. Comparative Example 3 The difference between this comparative example and Example 6 is that ZIF-67 is used as a carbon source, a conventional brushing method is adopted, and epoxy resin is used as a binder to prepare a hard carbon coating on the surface of the workpiece. The preparation method comprises the following steps: S1. 9.87 mmol of cobalt nitrate hexahydrate and 79.4 mmol of 2-methylimidazole were dissolved in 200 mL of methanol respectively; under stirring, the cobalt nitrate hexahydrate solution was quickly poured into 2-methylimidazole, stirred at room temperature for 1 h, centrifuged at 12000 rpm, washed with methanol 4 times, and vacuum dried at 60°C for 12 h to obtain ZIF-67; S2. Mix the ZIF-67 obtained in S1 with E51 epoxy resin in a mass ratio of 1:10. After mixing evenly, add 651 low molecular weight polyamide curing agent. The mass ratio of epoxy resin to 651 low molecular weight polyamide curing agent is 70:30. Mix evenly again and apply it evenly on the surface of the cleaned and dried graphite workpiece, and cure it at 120°C for 4h. The coating amount of the mixture is 0.06g / cm 2 ; S3. The graphite workpiece obtained in S2 is heat treated at 1100° C. for 2 h under inert gas protection to obtain a graphite workpiece with ZIF-67 derived hard carbon. Performance Testing 1. Specific surface area test, reference standard "GB / T 19587-2017" The surface coating of the graphite workpiece in each embodiment and the comparative example was mechanically peeled off by a scraper, and its specific surface area was analyzed by a fully automatic BET specific surface analysis tester. The results are shown in Table 1. The specific surface area of ​​the hard carbon coating obtained in Examples 1-6 is greater than 970 m 2 / g, the specific surface area of ​​the hard carbon coating obtained in Comparative Example 1 is 503m 2 / g, it can be seen that the hard carbon coating obtained by the present invention has a higher specific surface area and a richer pore structure. Table 1 Specific surface area of ​​Examples 1-6 and Comparative Example 1 <![CDATA[Specific surface area m 2 / g]]> Example 1 1083 Example 2 1025 Example 3 989 Example 4 1001 Example 5 975 Example 6 1072 Comparative Example 1 503 2. Tensile test required to destroy the coating, refer to the standard "GB / T 5210-2006" The adhesion test of the pull-off method was used to measure and evaluate the bonding strength and wear resistance of the coatings of Examples 1-6 and this comparative example. The test column was bonded to the coating surface with an adhesive. After the adhesive was cured, the bonded experimental combination was placed on a suitable pressure testing machine. The bonded experimental combination was subjected to a controlled tensile test to measure the tensile force required to destroy the coating / substrate, and the tensile force required to destroy the coating was used to represent the experimental results. The minimum tensile force required to destroy the coatings of Examples 1-6 was 1.0 MPa, and the tensile force required to destroy Comparative Example 2 was 0.4 MPa. It can be seen that the in-situ hard carbon coating obtained by the present invention has better coating bonding strength. Table 2 Tensile force required to destroy the coating of Examples 1-6 and Comparative Example 2 3. Test of coating metal ion content, reference standard "GB / T30902-2014" The surface coatings of the graphite workpieces in Examples 1-6 and Comparative Example 3 were mechanically stripped with a scraper, and the cobalt and zinc metal atom contents therein were detected using an inductively coupled plasma emission spectrometer (ICP). The metal atom contents of the coating parts in Examples 1-6 were all lower than the detection limit, and the metal atom mass accounted for 58.6% in the coating obtained in Comparative Example 3. There were almost no metal atoms remaining in the ZIF-8 derived carbon coatings obtained in Examples 1 to 6, mainly because the boiling point of metallic zinc was 907°C, and the zinc ions were reduced and evaporated during the heat treatment. The boiling point of metallic cobalt is 3100°C, and the cobalt ions cannot be evaporated after being reduced to metallic cobalt during the heat treatment of ZIF-67. In addition, the reduction-evaporation process of metallic zinc can also produce a pore structure, further increasing the specific surface area of ​​its derived hard carbon coating. Table 3 Metal ion content of coatings of Examples 1-6 and Comparative Example 3 Zinc atomic mass% Cobalt atomic mass% Example 1 0 0 Example 2 0 0 Example 3 0 0 Example 4 0 0 Example 5 0 0 Example 6 0 0 Comparative Example 3 0 58.6 Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. An in-situ hard carbon coating on the surface of a graphite workpiece, characterized in that: The hard carbon coating is a carbon coating derived from a ZIF-8 coating that is carbonized at high temperature. The ZIF-8 coating is prepared by in-situ solid phase reaction of zinc oxide and 2-methylimidazole that are electrochemically deposited on the surface of a graphite workpiece.

2. An in-situ hard carbon coating on the surface of a graphite workpiece, characterized in that: The preparation method comprises the following steps: S1. placing the cleaned graphite workpiece in an electrolyte and depositing zinc oxide on its surface by electrochemical deposition; S2. The graphite workpiece obtained in S1 was cleaned and dried, and then the surface was covered with ground 2-methylimidazole powder and placed in a sealed container for reaction; S3. The graphite workpiece obtained in S2 is cleaned and dried, and then heat-treated under the protection of an inert gas to obtain a graphite workpiece with a porous hard carbon coating.

3. The method for preparing an in-situ hard carbon coating on the surface of a graphite workpiece according to claim 2, characterized in that: The preparation method of the electrolyte in S1 comprises the following steps: S11. Add zinc chloride, potassium chloride and sodium dodecyl sulfate in a molar ratio of 5 to 10:10 to 50:0.5 to 1 to water and heat in a water bath, and stir to obtain a homogeneous solution; S12. Pass oxygen into the homogeneous solution and continue stirring for 0.5 to 1.5 hours to obtain an electrolyte.

4. The method for preparing an in-situ hard carbon coating on the surface of a graphite workpiece according to claim 2, characterized in that: The mass fraction of the homogeneous solution in S11 is 10-35wt%.

5. The method for preparing an in-situ hard carbon coating on the surface of a graphite workpiece according to claim 2, characterized in that: The electrochemical deposition method in S1 is a constant potential method or a constant current method. The potential of the constant potential method is -1.5 to -0.8 V (vs. SCE), the time is 5 to 15 min, the working electrode of the constant current method is the anode, and the current density is 10 to 100 mA / cm 2 , time is 5 to 20 minutes.

6. The method for preparing an in-situ hard carbon coating on the surface of a graphite workpiece according to claim 2, characterized in that: The particle size of the 2-methylimidazole powder after grinding in S2 is 50-200 μm, and the coverage of the 2-methylimidazole powder is 0.05-0.2 g / cm 2 The reaction temperature is 160-175°C and kept warm for 5-20 minutes.

7. The method for preparing an in-situ hard carbon coating on the surface of a graphite workpiece according to claim 2, characterized in that: The heat treatment temperature in S3 is 1100-2200° C., and the heat treatment time is 2-4 hours.